دور التكنولوجيا الحديثة في تحقيق التنمية المستدامة في ضوء رؤية مصر 2030 - والي، محمد فوزي رياض (مؤسسة أكاديميا جلوب للبحث العلمي والنشر الدولي, 2023)
تناولت هذه الورقة البحثية عرضا موجزا لمفهوم التنمية المستدامة، وأهم خصائصها، وأهدافها، فضلا عن تحديد أهم أبعاد التنمية المستدامة، وآليات تحقيقها، مع عرض لرؤية مصر 2030 والتأكيد على دور التكنولوجيا في تحقيق التنمية المستدامة سواء على المستوى الاجتماعي أو البيئي مع التأكيد على الآليات التكنولوجية الإجرائية التي يمكن أن تسهم في تحقيق التنمية المستدامة. This research paper dealt with a brief presentation of the concept of sustainable development, its most important characteristics, and objectives, as well as identifying the most important dimensions of sustainable development and the mechanisms for achieving them, with a presentation of Egypt's Vision 2030 and an emphasis on the role of technology in achieving sustainable development, whether on the social or environmental level, with an emphasis on technological mechanisms that can contribute to achieving sustainable development.
Keywords: وسائل الإتصالات -- تكنولوجيا المعلومات -- التنمية المستدامة -- رؤية مصر 2030